Explaining Local Policy Agendas Institutions, Problems, Elections and Actors - B. Mortensen, Peter; W. Loftis, Matt; B. Seeberg, Henrik (Comparative Studies of Political Agendas, 2022)
XII, 194 p. 31 illus.